2008
DOI: 10.1002/ijc.24045
|View full text |Cite
|
Sign up to set email alerts
|

A simple and effective method for cancer immunotherapy by inactivated allogeneic leukocytes infusion

Abstract: Allogeneic mixed leukocytes reaction has been reported to activate vast numbers of T lymphocytes and produce large amounts of type 1 cytokines that are linked to an initiation of antitumor immunity. Using poor immunogeneic B16-F10 and Lewis lung carcinoma (LLC) tumor model, we evaluated the effects of inactivated allogeneic leukocytes infusion (ALI) on the generation of antitumor immune response, as well as its effect on the primary and metastatic tumor. Allogeneic response promoted the generation of both spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…Likewise, our data revealed that host antitumor activity of DLI was reinforced after adoptive transfer of donor cells, resulting in the proliferation of host lymphocytes especially the CD8+ T and NK cells. Furthermore, it has been reported that donor cell infusion can induce the activation and proliferation of lymphocytes that is coupled with an upregulation of Th1 cytokines, thus [21]. Similarly, we found that DLI treatment remarkably enhanced the secretion of sera IL-2 and IFN-γ, whereas imparted little effect on the IL-4 and IL-10 production.…”
Section: Discussionsupporting
confidence: 57%
“…Likewise, our data revealed that host antitumor activity of DLI was reinforced after adoptive transfer of donor cells, resulting in the proliferation of host lymphocytes especially the CD8+ T and NK cells. Furthermore, it has been reported that donor cell infusion can induce the activation and proliferation of lymphocytes that is coupled with an upregulation of Th1 cytokines, thus [21]. Similarly, we found that DLI treatment remarkably enhanced the secretion of sera IL-2 and IFN-γ, whereas imparted little effect on the IL-4 and IL-10 production.…”
Section: Discussionsupporting
confidence: 57%
“…These results led to the hypothesis that host antidonor immune responses might, under some conditions, induce regression of recipient tumors. Experiments of Su et al [20] demonstrate that introveinous infusion of mitotically inactivated allogeneic lymphocytes resulted in increased release of type-1 cytokines (including interleukin-2 and IFN-c), proliferation of various lymphocyte subsets, and generation of antitumor immune response. Rubio et al [21] explored this question in mice by administering recipient leukocyte infusions (RLIs) to mixed chimeras established with nonmyeloablative conditioning.…”
Section: Discussionmentioning
confidence: 98%
“…To examine the chemoprevention effect of ABP in vivo, we used the LLC murine artificial pulmonary metastatic model whose subcutaneous carcinoma LLC tumors were surgically removed and lung metastasis is caused by blood CTC. 5 The number of tumor nodules on the lung surface in the ABP-treated group was significantly reduced compared to the control group (Fig. 1k).…”
Section: Dear Editormentioning
confidence: 87%